Cell-type specific effects of the long non-coding RNA HIF1A-AS3 on HIF1A expression in kidney cells - Simone Reichelt-Wurm; Lena Knauss; Bettina Strasser; Mona Scharf; Kathrin Holler; Elke Eggenhofer; Markus Kretz; Bernhard Banas; Miriam C. Banas (Scientific Reports)
Abstract The hypoxia-inducible factor 1α (Hif1α) represents the master transcription factor coordinating cellular responses to oxygen depletion. With hundreds of target genes it plays a key role in numerous bio-medical conditions as well as neoplastic and non-cancerous diseases, which in turn requires a strict regulation. Long non-coding RNAs have the potential to virtually control every step of gene expression. We aimed to investigate the expression and role of HIF1A antisense lncRNAs HIF1A-AS1, AS2, and AS3 under hyperglycemic, hypoxic, or both conditions in three non-cancerous human renal cell types: HK-2 cells, primary RPTECs, and mesangial cells. We observed that HIF1A-AS2 and AS3 expression was upregulated under oxygen deprivation. Furthermore, knockdown (KD) of HIF1A-AS3 resulted in a significant reduction of HIF1A-AS2 and even more important of Hif1α in HK-2 cells but not mesangial cells. While KD of HIF1A also had a diminishing effect on HIF1A-AS2 and AS3 RNA levels, KD of HIF1A-AS2 only affected HIF1A-AS3 but not HIF1A. Treating HK-2 cells with Actinomycin D revealed a high HIF1A-AS3 RNA stability. In conclusion, our data reveal a cell-type specific effect of HIF1A-AS3 on HIF1A RNA and protein expression which might allow the development of a cell-type specific HIF1A antagonist based on lncRNAs.